Sukan Antara Fakulti (SAF) FPHP 2024 - "Together We Achieve More"/ Irina Mohd Akhir … [et al.] - Mohd Akhir, Irina; Rahim, Noraini; Mahat, Fadhlina; Abd Rahman, Rabiatul Adawiyah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
As FPHP SAF team dive into the exciting journey of Sukan Antara FakuIti (SAF) 2024, our theme, "Together We Achieve More," resonates deeply within the Faculty of Hotel and Tourism Management (FPHP). Under the dedicated leadership of Mr. Dahlan Abdullah, our contingent leader, we have built a dynamic team of managers and coaches who embody the spirit of teamwork and dedication.